Be quiet and man up: a qualitative questionnaire study into fathers who witnessed their Partner's birth trauma - Emily Daniels; Emily Arden-Close; Andrew Mayers (BMC, 2020)
Abstract Background Research focusing on paternal mental health is limited, especially regarding the impact of the experience of poor mental health in the perinatal period. For example, little is known about the experiences of fathers who witness their partner's traumatic birth and the subsequent impact on their mental health. Therefore, the aim of this study was to explore fathers' experiences of witnessing a traumatic birth, how these experiences impacted their wellbeing, and what support they received during and following the traumatic birth. Methods Sixty-one fathers were recruited via targeted social media to complete an anonymous online qualitative questionnaire regarding their birth trauma experience. Eligible participants were fathers aged eighteen or over, resided in the UK and had witnessed their partner's traumatic birth (that did not result in loss of life). Thematic analysis was used to analyse the questionnaire data. Results Three main themes were identified: 'fathers' understanding of the experience' (subthemes: nothing can prepare you for it; merely a passenger; mixed experiences with staff; not about me); 'life after birth trauma' (subthemes: manhood after birth; inability to be happy; impact on relationships); and 'the support fathers received vs what they wanted' (subthemes: prenatal support; birth support; and postnatal support). Conclusions Fathers reported that witnessing their partner's traumatic birth had a significant impact on them. They felt this affected their mental health and relationships long into the postnatal period. However, there is no nationally recognised support in place for fathers to use as a result of their experiences. The participants attributed this to being perceived as less important than women in the postnatal period, and maternity services' perceptions of the father more generally. Implications include ensuring support is available for both the mother and father following a traumatic birth, with additional staff training geared towards the father's role.